Low Prevalence of Coagulation and Fibrinolytic Activation in Patients with Primary Untreated Cancer - Nanninga, P B; van Teunenbroek, A; Veenhof, C H N; Büller, H R; ten Cate, J W (Thrombosis and Haemostasis, 1990)
The prevalence of subclinical coagulation abnormalities greatly differs in the various studies due to selection of patients and differences in study design. We performed coagulation studies in 69 consecutive patients with primary untreated cancer of various origin. The control group consisted of 42 sex and age matched healthy volunteers. Plasma coagulation tests included thrombin-antithrombin-III-complex (TAT), plasmin-alpha2-antiplasmin-complex (PAP) and tissue-plasminogen-activator-antigen (t-PA-ag). These tests were performed once, prior to any anti-cancer treatment. We evaluated if activation of the coagulation system (elevated TAT-complexes) and the fibrinolytic system (elevated PAP-complexes and t-PA-ag) correlated with the tumor-type or the extent of the tumor. To document clinical manifest haemorrhage or thromboembolic disease (TED) we performed a 6 months follow-up study.In 8 patients (12%) and in 3 control subjects (7%) an elevated TAT-complex level was observed (this difference is not significant). An increased plasma level of PAP-complex was seen in 8 patients (12%) versus none in the control group (p <0.05). In one patient both TAT and PAP-complex concentrations were elevated. Consequently, 15 of the 69 patients (22%) showed activation of the coagulation and/or fibrinolytic system.Fibrinolysis seems to be enhanced in a subset of cancer patients in contrast to blood coagulation.In 10 patients (14%) we found raised t-PA-ag levels. Three patients had both elevated levels of PAP-complex and t-PA-ag. These findings suggest that in a minority of patients increased PAP-complex levels may be a result of t-PA induced plasminogen activation. No preferential association was found between tumortype and activation of these systems.During follow-up we encountered in only 4 patients (6%) clinical evidence of haemorrhage or TED.We conclude that a subclinical coagulopathy is present in approximately a fifth (22%, 95 percent confidence limits 13-33%) of untreated primary cancer patients.